Unraveling Genetic Diversity Amongst European Hazelnut (Corylus avellana L.) Varieties in Turkey - Oztolan-Erol, Nihal; Helmstetter, Andrew J.; İnan, Asuman; Buggs, Richard J. A.; Lucas, Stuart J. (Frontiers in Plant Science, 2021)
European hazelnut (Corylus avellana) is a diploid (2n=22), monoecious and wind-pollinated species, extensively cultivated for its nuts. Turkey is the world-leading producer of hazelnut, supplying 70%-80% of the world’s export capacity. Hazelnut is mostly grown in the Black Sea Region, and maintained largely through clonal propagation. Understanding the genetic variation between hazelnut varieties, and defining variety-specific and disease resistance-associated alleles, would facilitate hazelnut breeding in Turkey. Widely grown varieties ‘Karafındık’ (2), ‘Sarıfındık’ (5), and ‘Yomra’ (2) were collected from Akçakoca in the west, while ‘Tombul’ (8), ‘Çakıldak’ (3), ‘Mincane’ (2), ‘Allahverdi’ (2), ‘Sivri’ (4), and ‘Palaz’ (5) were collected from Ordu and Giresun provinces in the east (numbers in parentheses indicate sample sizes for each variety). Powdery mildew resistant and susceptible hazelnut genotypes were collected from the field gene bank and heavily infected orchards in Giresun. Every individual was subjected to double digest restriction enzyme-associated DNA sequencing (ddRADseq) and a RADtag library was created. RADtags were aligned to the ‘Tombul’ reference genome, and Stacks software used to identify polymorphisms. 101 private and six common alleles from nine hazelnut varieties, four private from resistants and only one from susceptible were identified for diagnosis of either a certain hazelnut variety or powdery mildew resistance. Phylogenetic analysis and population structure calculations indicated that ‘Mincane’, ‘Sarıfındık’, ‘Tombul’, ‘Çakıldak’ and ‘Palaz’ were genetically close to each other; however, individuals within every varietal group were found in different sub-populations. Our findings indicated that years of clonal propagation of some preferred varieties across the Black Sea Region has resulted in admixed sub-populations and great genetic diversity within each variety. This impedes the development of a true breeding variety. For example, ‘Tombul’ is the most favoured Turkish variety because of its high quality nuts, but an elite ‘Tombul’ line does not yet exist. This situation continues due to the lack of a breed protection program for commercially valuable hazelnut varieties. This study provides molecular markers suitable for establishing such a programme.